Proposal of descriptors for the characterisation of Jatropha curcas - Vinícius Magro dos Reis, Marcus (Revista Ciência Agronômica, 2021)
Despite the importance of the physic nut (Jatropha curcas) in biodiesel production, knowledge of its genetic variability is still in the early stages, with the development of descriptors bring essential to achieving this goal. The aim of this study, therefore, was to propose and develop a list of standardised and tested descriptors, and to indicate those that make the greatest contribution to characterising the physic nut. Fifty-three morphological and reproductive descriptors of a quantitative, multi-category or binary nature were proposed. Descriptive estimates were obtained from among the descriptors. Using PCA, highly correlated descriptors were discarded. Then, the descriptors with the greatest relative contribution to estimating genetic diversity among the plants under analysis were identified. Reproductive descriptors had the highest coefficients of variation. Of 38 quantitative descriptors, 19 were sufficient to discriminate between the plants. This covered production, the crown of the plant, inflorescences, and fruit maturation. Descriptors related to grain yield, the uniformity of maturation and the crown showed the greatest relative contributions to diversity. Of the 13 multi-category descriptors, only five vegetative descriptors were discriminative. None of the proposed binary descriptors showed anyvariation.